2022
DOI: 10.52019/ijpt.v1i2.3322
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas Mirror Therapy Exercise Terhadap Kemampuan Fungsional Wajah Penderita Facial Palsy : Studi Literatur

Abstract: Latar Belakang : Facial palsy adalah suatu kondisi neurologis yang memengaruhi fungsi motorik wajah ditandai dengan asimetri dan kelemahan otot sebagian atau seluruh wajah sehingga menurunkan kemampuan fungsional wajah. Mirror therapy exercise merupakan suatu latihan berupa senam wajah dengan meggunakan cermin atau software untuk menghasilkan umpan balik visual  dari bagian tubuh yang terkena lesi dan menghasilkan gerakan di sisi tubuh yang terkena. Tujuan :  Untuk mengetahui efektivitas  mirror therapy exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…Mirror exercise is a therapeutic intervention that focuses on moving undamaged or injured body parts using a mirror, which aims to provide sensory feedback to encourage learning in the patient's healing process. Mirrors are used to convey visual stimuli to the brain through observing unaffected parts of the body while the individual performs a series of movements (Munawwarah et al, 2021). It can be concluded that the healing mirror exercise uses facial exercises on the side of the lesion (abnormal on the body) in front of the mirror and can prevent muscle atrophy so that it can improve muscle function and speed up the healing process for patients with Bell's palsy and in mirror exercise the role of physiotherapy in cases Bell's palsy is moving the facial muscles with mirror feedback which is used to convey visual stimulation to the brain by observing the part of the body that is experiencing weakness so that the individual is affected and carries out a series of movements (Astuti & Rahman, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Mirror exercise is a therapeutic intervention that focuses on moving undamaged or injured body parts using a mirror, which aims to provide sensory feedback to encourage learning in the patient's healing process. Mirrors are used to convey visual stimuli to the brain through observing unaffected parts of the body while the individual performs a series of movements (Munawwarah et al, 2021). It can be concluded that the healing mirror exercise uses facial exercises on the side of the lesion (abnormal on the body) in front of the mirror and can prevent muscle atrophy so that it can improve muscle function and speed up the healing process for patients with Bell's palsy and in mirror exercise the role of physiotherapy in cases Bell's palsy is moving the facial muscles with mirror feedback which is used to convey visual stimulation to the brain by observing the part of the body that is experiencing weakness so that the individual is affected and carries out a series of movements (Astuti & Rahman, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Senam wajah dilaksanakan bersama-sama dengan posisi duduk tegap di kursi, rileks, kondisi tenang dan nyaman, dipandu peneliti dan diawasi oleh instruktur. [10], [11]…”
Section: Metode Penelitianunclassified